The arabidopsis WAVE/SCAR protein BRICK1 associates with cell edges and plasmodesmata - Zhihai Chi; Chris Ambrose (PLoS ONE, 2025)
Plasmodesmata are specialized structures in plant cell walls that mediate intercellular communication by regulating the trafficking of molecules between adjacent cells. The actin cytoskeleton plays a pivotal role in controlling plasmodesmatal permeability, but the molecular mechanisms underlying this regulation remain unclear. Here, we report that BRK1, a component of the WAVE/SCAR complex involved in Arp2/3-mediated actin nucleation, localizes to PD and primary pit fields in A. thaliana cotyledons, leaves, and hypocotyls. Using a BRK1-YFP reporter line, we detected BRK1 enrichment at cell edges and in primary pit fields, identified by regions of reduced propidium iodide staining. We also observed colocalization between BRK1-YFP and the plasmodesmatal callose stain aniline blue, further supporting BRK1’s association with Plasmodesmata. Together, these findings suggest that the WAVE/SCAR complex participates in plasmodesmatal regulation by promoting ARP2/3-dependent actin filament branching at plasmodesmata, complementing the role of linear actin stabilization by formins.